TINGKAT KESADARAN EKOLOGIS MASYARAKAT KAMPUNG LAUT, KABUPATEN CILACAP, JAWA TENGAH - Endang Sulastri; Trisakti Haryadi; Elyvia Inayah (Jurnal Kawistara, 2019)
This study examined the level of ecological awareness of the community in Kampung Laut, Cilacap, which is seen from the aspects of sensitivity, responsibility, and cooperation. The selection of Kampung Laut Sub-districtbased on the consideration that it was an area that directly affected by the silting of Segara Anakan Lagoon as well as the implementation area of the Community Empowerment Program. Ecological awareness is a perspective that used as a basis for determining operational limits. Ecological awareness is one of the efforts that should be instilled in society as a form of conservingthe environment. The concept of community development became a supporting theory to analyze results. Survey and focus group discussion (FGD) used as method in this research. Retrieval 76 respondents refer to the sample framework which lists the names of perpetrators and beneficiaries of the Community Empowerment Program. This research was carried out in some hamlets such as Panikel, Bugel, Pelindukan, and Cikerang with the consideration that those hamlets received the Community Empowerment Program. The result of this research showed that the level of ecological awareness of the community in Kampung Laut, Cilacap was in the medium and high category. This showed that the community has a good awareness in caring for and preserving the environment. Efforts to increase the ecological awareness of the people in Laut Kampung Laut pursued by increasing the motivation through trainings in order to raise public awareness to for better environment in the future.